Investigation of bioactive chemical constituents and anti-cancer activity of ethanol extract of Curcuma singularis Gagnep rhizomes. Issue 18 (8th September 2022) - Doan, Chinh Chung; Le, Thanh Long; Ho, Nguyen Quynh Chi; Tran, Thi Linh Giang; Le, Nguyen Tu Linh; Vu, Quang Dao; La, Thi Hong Lan; Nguyen, Viet Cuong; Nguyen, Thi Phuong Thao; Hoang, Nghia Son
Abstract: Curcuma singularis Gagnep is a Vietnamese medicinal plant which has been commonly used in traditional and folk medicines for the treatment of different diseases. The goals of the present study are to investigate chemical composition and anti-proliferative activity of Curcuma singularis rhizome extract (CSE). The in vitro cytotoxicity of CSE was evaluated using WST-1 and LDH assays. The apoptosis induction was determined using nuclei DAPI staining and FACS assays. The main compounds of extract were identified and quantitatively analyzed using the validated HPLC method. The extract showed cytotoxic effects in various liver and breast cancer cells but had minimal effects on normal cells. It induced apoptosis on both Hep3B and SKBR3 cells in a dose-dependent manner. In addition, three sesquiterpene compounds, such as germacrone (3.25 ± 0.32 mg/g), ar-turmerone (1.12 ± 0.24 mg/g), and curcumol (0.31 ± 0.12 mg/g) were found as the main components of CSE. This is the first report on the in vitro cytotoxic effect of Curcuma singularis rhizomes against cancer cells. Graphical abstract: UF0001